STUDI LITERATUR EFEKTIVITAS GYMBALL UNTUK MEMICU KONTRAKSI PADA IBU INPARTU DI PUSKESMAS MPUNDA KOTA BIMA TAHUN 2025 - Ema Elvinawati; Sri Astuti; Muhammad Affan (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2025)
Introduction : Childbirth can become pathological and endanger the mother and fetus if the mother is very afraid and anxious about giving birth. Fear will affect the length of labor, poor contractions, and lack of dilation. Gymballs are very useful for advancing labor, lowering the head, and reducing pain, thereby relaxing the mother. In 2023, the maternal mortality rate (MMR) was 177/100,000 live births and the infant mortality rate was 6/1000 live births. In 2024, the maternal mortality rate (MMR) was 86 per 100,000 live births and the infant mortality rate was 11 per 100 live births (Health Office, Bima City 2024). The causes of maternal mortality in Bima City were hepatitis, chronic asthma, and cardiovascular disorders, while the indirect causes of the main causes of maternal mortality were 3 out of 6 cases of maternal mortality, 2 cases due to hemorrhage, and 1 case due to hypertension in pregnancy (Bima City Health Office, 2018). The direct factors causing high MMR are hemorrhage (45%), particularly postpartum hemorrhage, pregnancy poisoning (24%), infection (11%), and prolonged/stalled labor (7%). (Umairo & Anita, 2022). Research Objective: To identify the effectiveness of gymballs in inducing contractions in women in labor. Research Method: This study used a literature review method. Data sources: Searches using Google Scholar and Semantic Scholar published in Indonesian in the last 5 years, from 2020 to 2025. Results And Conclusions: A literature review of 12 selected journals showed that gymballs are effective in reducing anxiety (painful), accelerating head descent/time of delivery.